Pro-Tumorigenic Macrophage Infiltration in Oral Squamous Cell Carcinoma and Possible Macrophage-Aimed Therapeutic Interventions - Bruna, Flavia; Scodeller, Pablo (Frontiers in Oncology, 2021)
In Oral Squamous Cell Carcinomas (OSCC), as in other solid tumors, stromal cells strongly support the spread and growth of the tumor. Macrophages in tumors (tumor-associated macrophages or “TAMs”), can swing between a pro-inflammatory and anti-tumorigenic (M1-TAMs) state or an anti‐inflammatory and pro-tumorigenic (M2-TAMs) profile depending on the tumor microenvironment cues. Numerous clinical and preclinical studies have demonstrated the importance of macrophages in the prognosis of patients with different types of cancer. Here, our aim was to review the role of M2-TAMs in the prognosis of patients with OSCC, and provide a state of the art on strategies for depleting or reprogramming M2-TAMs as a possible therapeutic solution for OSCC. The Clinical studies reviewed showed that higher concentrations of CD163+ M2-TAMs associated with worse survival and that CD206+ M2-TAMs are involved in OSCC progression through epidermal growth factor (EGF) secretion, underlining the important role of CD206 as a marker of OSCC progression and as a therapeutic target. Here, we provide the reader with the current tools, in preclinical and clinical stage, for depleting M2-TAMs, re-educating them towards M1-TAMs, and exploiting TAMs as drug delivery vectors. Notably, we found no preclinical studies on the effects of targeting M2-TAMs for treating OSCC, suggesting that M2-TAMs-aimed interventions might be useful in the management of OSCC.